Composition, synthesis and use of EMM-70 zeolite

The synthesis of zeolites like EMM-70 with controlled internal pore configurations addresses the need for improved selectivity and efficiency in gas separation and organic conversion processes, achieving enhanced performance and cost-effectiveness.

JP2025502413APending Publication Date: 2025-01-24EXXONMOBIL TECHNOLOGY & ENGINEERING CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024543008
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-21
Filing Date
2023-01-06
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

There is a need for new zeolites with specific internal pore configurations and improved selectivity for applications such as gas separation, drying, and organic conversion processes, as well as more efficient methods to synthesize molecular sieves with reduced costs.

Method used

The method involves synthesizing zeolites like EMM-70, which includes forming a synthetic mixture with specific ratios of elements and a structure-directing agent, crystallizing under controlled conditions, and removing the agent to achieve desired X-ray diffraction patterns and properties, such as high micropore volume and surface area.

Benefits of technology

The method produces zeolites with enhanced selectivity and efficiency for organic conversions and gas separations, offering improved performance and reduced production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502413000021
    Figure 2025502413000021
  • Figure 2025502413000022
    Figure 2025502413000022
  • Figure 2025502413000023
    Figure 2025502413000023
Patent Text Reader

Abstract

A zeolite (designated EMM-70) characterized by a unique powder XRD pattern, a process for producing said zeolite, and uses of said zeolite.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims the benefit of and priority to U.S. Provisional Application No. 63 / 301,705, filed Jan. 21, 2022, the disclosure of which is incorporated herein by reference.

[0002] (Technical field) The present disclosure relates to compositions of zeolites, methods for making such zeolites, and uses of such zeolites. [Background technology]

[0003] BACKGROUND OF THEINVENTION Molecular sieve materials, whether natural or synthetic, can be used as adsorbents and can have catalytic properties in reactions of hydrocarbon conversion. Certain molecular sieves, e.g., zeolites, AlPO, and mesoporous materials, are ordered, porous, crystalline materials that have a well-defined crystal structure as determined by X-ray diffraction (XRD). A particular molecular sieve gives rise to an orderly and specific recognizable (or distinguishable or identifiable or identifiable) XRD pattern. Within a particular molecular sieve material, there may be a number of cavities (or voids or void spaces) that may be connected (or interconnected) to one another by a certain number of channels or pores (or holes or pores). Such cavities and pores are uniform in size (or dimension or size) within a particular molecular sieve material. Because the dimensions of the pores are such that, for example, they accept adsorbed molecules having certain dimensions while rejecting molecules having larger dimensions, such materials have come to be known as "molecular sieves" and are used in a variety of industrial processes (e.g., cracking, hydrocracking, disproportionation, alkylation, oligomerization, and isomerization).

[0004] Molecular sieves find use in catalysis and adsorption. Molecular sieves include both natural and synthetic crystalline molecular sieves. Examples of such molecular sieves include large pore zeolites, intermediate pore size zeolites, and small pore zeolites. Such zeolites and their isotypes have been classified by the Structure Commission of the International Zeolite Association according to the rules of the IUPAC Commission on Zeolite Nomenclature. By this classification, framework-type zeolites and other crystalline, microporous molecular sieves have been assigned three-letter codes (and therefore structures established) and are described in the following literature: Ch. Baerlocher, LB McCusker, and DH Olson, eds. (2007) Atlas of Zeolite Framework Types, ed. Elsevier, 6th Edition, which is incorporated herein by reference. Such zeolites and their isotypes are also described below. http: / / america.iza-structure.org / IZA-SC / ftc_table.php. Large pore zeolites generally have a pore size (or pore diameter or pore size or pore size) of at least about 7 Å (angstroms). Included are LTL, VFI ("extra large" 18R), MAZ, FAU, OFF, *BEA and MOR framework type zeolites. Examples of large pore zeolites include mazzite, offretite, zeolite L, VPI-5, zeolite Y, zeolite X, omega (ω), and beta (β). Intermediate pore size zeolites generally have a pore size (or pore diameter) of about 5 Å to less than about 7 Å, and include, for example, MFI, MEL, EUO, MTT, MFS, AEL, AFO, HEU, FER, MWW, and TON framework type zeolites. Examples of intermediate pore size zeolites include ZSM-5, ZSM-11, ZSM-22, MCM-22, silicalite-1 and silicalite-2. Small pore size zeolites have a pore size (or pore diameter or pore size or fine pore size) of about 3 Å to less than about 5.0 Å, examples of which include CHA, RTH, ERI, KFI, LEV, SOD, and LTA framework type zeolites. Examples of small pore zeolites include ZK-4, ZSM-2, SAPO-34, SAPO-35, ZK-14, SAPO-42, ZK-21, ZK-22, ZK-5, ZK-20, zeolite A, chabazite, zeolite T, and ALPO-17.

[0005] The idealized inorganic framework structure of a zeolite is a silicate framework in which every tetrahedral atom is connected (or bonded) to the four next nearest tetrahedral atoms (or tetrahedral atoms) by oxygen atoms. The term "silicate" as used herein means a material that contains at least silicon atoms and oxygen atoms, the silicon atoms and the oxygen atoms being alternately bonded to each other (i.e., -O-Si-O-Si-), and optionally other atoms, such as boron, aluminum or other metals, such as transition metals, such as titanium, vanadium or zinc. In framework silicates, atoms other than silicon and oxygen occupy some of the lattice sites, otherwise occupied by silicon atoms (or silica atoms), in "all-silica" framework silicates. Thus, the term "framework silicate" as used in this disclosure means a lattice of atoms (or atomic lattice) including any of silicate, borosilicate, gallosilicate, ferrisilicate, aluminosilicate, titanosilicate, zincosilicate, vanadosilicate, and the like.

[0006] In a given zeolite, the structure of the framework silicates determines the size (or magnitude or dimension) of the pores (or holes or pores) or channels present therein. The size (or dimension or size) of the pores (or holes or pores) or channels can determine the type (or type) of process (or method) for which a given zeolite is applicable (or adaptable or applicable). Currently, over 200 unique zeolite framework silicate structures are known. Such structures have been recognized by the Structure Commission of the International Zeolite Association, thereby defining a range of pore geometries and orientations.

[0007] Zeolite framework silicates are commonly characterized with respect to the size of their rings, meaning the number of silicon atoms (or alternative atoms, such as those listed above) that are tetrahedral coordinated with oxygen atoms as loops, defining pores or channels within the zeolite. For example, an "8-ring" zeolite means a zeolite having pores or channels defined by eight alternating tetrahedral atoms and eight oxygen atoms in a loop. The pores or channels defined in a given zeolite may be symmetric or asymmetric, depending on the various structural constraints present in the particular framework silicate.

[0008] The synthesis of molecular sieve materials typically involves hydrothermal crystallization from a synthesis mixture that contains sources of all the elements present in the zeolite (e.g., a source of alumina as well as a source of silica). In many cases a structure directing agent (SDA) is also present. A structure directing agent is a compound believed to facilitate the formation (or production) of a molecular sieve, such a compound is believed to act as a template, around which a particular molecular sieve structure can be formed (or produced), thereby facilitating the formation (or production) of a desired molecular sieve. A variety of compounds have been used as structure directing agents, including various kinds (or types) of quaternary ammonium cations. Typically, zeolite crystals form around a structure directing agent, which occupies pores in the zeolite once crystallization is complete. Thus, an "as-synthesized" zeolite contains a structure directing agent within its pores. Therefore, after crystallization, the "as-synthesized" zeolites are usually subjected to a treatment step, such as a calcination step, to remove such structure directing agents.

[0009] For example, WO 2004 / 013042 A1 discloses the preparation of molecular sieves SSZ-64 prepared using structure directing agents of the N-cyclobutylmethyl-N-ethylhexamethyleneiminium cation or the N-cyclobutylmethyl-N-ethylheptamethyleneiminium cation. Summary of the Invention [Problem to be solved by the invention]

[0010] Although many different zeolites have been discovered, there is a continuing need for new zeolites that have desirable properties for gas separation, drying, organic conversion reactions, and other uses. The new zeolites may contain new internal pore architectures that may provide improved selectivity in such processes. It is also important to discover new structure directing agents and more effective methods for synthesizing molecular sieves to facilitate the preparation of new molecular sieves and / or reduce the cost of producing known zeolites. [Means for solving the problem]

[0011] (Abstract) The present disclosure relates to zeolites, methods for making such zeolites, and uses (or methods of using) such zeolites. In a first embodiment, the present disclosure relates to a zeolite which, in its as-calcined (or calcined or calcined or calcined) form (e.g., in which at least a portion of the SDA has been removed), has an X-ray diffraction pattern including the peaks (2θ(°)) shown in Table 1 below.

[0012] [Table 1]

[0013] In a second embodiment, the present disclosure relates to a zeolite having, in its as-synthesized form (e.g., in which the SDA has not been removed), an X-ray diffraction pattern including the peaks (2θ(°)) shown in Table 2 below.

[0014] [Table 2]

[0015] In a third embodiment, the present disclosure relates to a method for producing a zeolite. In particular, the present disclosure relates to a method for producing a zeolite of the first or second embodiment, the method comprising the following steps (or steps) (a) to (d): (a) A process for preparing a synthesis mixture, the synthesis mixture comprising water, a source of an oxide of a tetravalent element (Y), a source of an oxide of a trivalent element (X), a structure directing agent (Q), optionally a source of hydroxide ions (OH), optionally a source of alkali metal and / or alkaline earth metal elements (M), and optionally a source of fluoride (F); The structure directing agent (Q) has the following formula I: [ka] (Formula I) [In the formula, R is methyl or ethyl] and wherein the cation is selected from the group consisting of 4,5,6,7-tetrahydrobenzimidazolium cations a molar ratio of Y / X in the synthesis mixture is less than 30, and if a source of fluoride (F) is present, the molar ratio of F / Y is less than 0.05; (b) heating the synthesis mixture under crystallization conditions comprising a temperature of 100°C to 200°C for a time period sufficient to form zeolite crystals; (c) recovering at least a portion of the zeolite from step (b); and (d) Optionally, a step (or steps) of treating the zeolite recovered in step (c) to remove at least a portion of the structure directing agent (Q).

[0016] In a fourth embodiment, the present disclosure relates to a process (or method or step) for converting (or converting or converting or converting) an organic compound to a conversion product (or conversion product or conversion product), comprising contacting (or a step or step) an organic compound with a zeolite according to the first or second embodiment, or a zeolite prepared (or prepared or manufactured) according to the process (or method or step) of the third embodiment.

[0017] These and other features and characteristics of the present disclosure, as well as their advantageous uses (or adaptations or adaptations or applications) and / or uses (or methods of use), will be apparent from the following detailed description. Of course, it will be understood that features described in connection with one aspect of the invention may be incorporated in other aspects of the invention. In particular, two or more features described in this specification (features included in a section (or chapter) of this Summary) may be combined in any manner to form a combination (or combination) of features not specifically described in this disclosure. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 shows an SEM image of the product of Example 2 (as-synthesized or as-synthesized). [Diagram 2] FIG. 2 shows the powder XRD pattern of the product of Example 5 (as-synthesized or as-synthesized). [Diagram 3] FIG. 3 shows the powder XRD pattern of the product of Example 5 (as-calcined or as-calcined). [Figure 4]FIG. 4 shows an SEM image of the product of Example 5 (as-synthesized or as-synthesized). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] (Detailed Description) The present disclosure relates to compositions of zeolites, methods for making such zeolites, and uses of such zeolites, which may be designated as EMM-70 zeolite or EMM-70 material.

[0020] In a first embodiment, the present disclosure relates to a zeolite which, in its as-calcined (or calcined or calcined or calcined) form (e.g., in which at least a portion of the SDA has been removed), has an X-ray diffraction pattern including the peaks (2θ(°)) shown in Table 1 below.

[0021] [Table 3]

[0022] As a further embodiment, the zeolite may have an X-ray diffraction pattern in its as-calcined form (or as-calcined form or calcined form or calcined form) that includes the peaks (2θ(°)) shown in Table 1A below. Here, the values ​​of the distance d (d-spacing) have a deviation determined based on their corresponding deviation (±0.20(2θ(°))) when converted to the corresponding value to obtain the distance d using Bragg's law.

[0023] [Table 4]

[0024] The XRD patterns having XRD peaks described in this disclosure use Cu(Kα) radiation.

[0025] In one or more further embodiments, the zeolite, in its calcined form (or as-calcined form or calcined form or calcined form), may have a micropore volume (or micropore volume or micropore volume) of 0.05 to 0.3, such as 0.1 to 0.25, such as 0.18 cc / g.

[0026] In one or more further embodiments, the zeolite has a melting point of 100 to 800 ml in its calcined form (or as-calcined or calcined or calcined form). 2 / g, e.g., 300-600m 2 / g, e.g., 505m 2 / g micropore surface area (or micropore surface area or micropore surface area) and / or 5 to 200 m 2 / g, e.g., 20-100m 2 / g, e.g., 63m 2 / g of external surface area.

[0027] In one or more further embodiments, the zeolite, in its calcined form (or as-calcined form or calcined form or calcined form), may optionally be represented by the molecular formula of Formula II below. (m)X2O3:YO2 (formula II) In the formula, 0.017≦m≦0.1. X is a trivalent element. Y is a tetravalent element. Y may include one or more of Si and Ge. For example, Y may include or be Si. X may include one or more of Al and B. For example, X may include or be Al and / or B. In particular, X may include or be Al. In formula II, the oxygen atom may be replaced with a carbon atom (e.g., in the form of CH2), which may come from the source of the ingredients (or components) used to prepare (or prepare or manufacture) the as-made zeolite. Also, in formula II, the oxygen atom may be replaced with a nitrogen atom, for example after removal of the SDA. Formula II may represent a typical zeolite framework as defined in this disclosure in its as-calcined or calcined form and is not intended as a solo representation of the zeolite. The zeolite, in its as-calcined or calcined form, may contain SDA and / or impurities after appropriate treatment to remove SDA and impurities not accounted for in formula II. Furthermore, Formula II does not include any charge or hydrogen (or proton) compensating ions that may be present in the zeolite upon calcination.

[0028] The variable m is the molar ratio that represents the relationship of X2O3:YO2 (or X2O3 / YO2) in Formula II. For example, when m is 0.025, the molar ratio of YO2:X2O3 (or YO2 / X2O3) is 40 and the molar ratio of Y:X (or Y / X) is 20 (e.g., the molar ratio of Si / Al is 20). m may vary and may be between 0.017 and 0.1, for example at least 0.017, or at least 0.020, or at least 0.025 up to 0.1, or up to 0.05, for example 0.033. The molar ratio of Y:X (Y / X) may be from 1 to less than 30, such as at least 5, or at least 10, and up to 29, or up to 25, or up to 20, such as 15.

[0029] In a second embodiment, the present disclosure relates to a zeolite, in particular as defined in the first embodiment, which in its as-synthesized form (e.g., in which the SDA has not been removed) has an X-ray diffraction pattern including the peaks (2θ(°)) shown in Table 2 below.

[0030] [Table 5]

[0031] In a further embodiment, the zeolite may have an X-ray diffraction pattern in its as-synthesized form (or as-synthesized or synthesized form) that includes the peaks (2θ(°)) shown in Table 2A below. Here, the values ​​of the distance d (d-spacing) have a deviation determined based on their corresponding deviation (±0.20(2θ(°))) when converted to the corresponding value to obtain the distance d using Bragg's law.

[0032] [Table 6]

[0033] The XRD patterns having XRD peaks described in this disclosure use Cu(Kα) radiation.

[0034] In one or more further embodiments, the zeolite, in its as-synthesized form (or as-synthesized or synthesized form), may optionally be represented by the molecular formula of Formula III below. (q) Q:(m) X2O3:YO2 (Formula III) During the ceremony, 0≦q≦0.5, 0.017 <m≦0.1であり、 at least one cation selected from the 4,5,6,7-tetrahydrobenzimidazolium cations of formula I: [ka] (Formula I) [In the formula, R is methyl or ethyl] X is a trivalent element (as defined in formula II); Y is a tetravalent element (as defined in formula II). Formula III may represent a typical zeolite framework as defined in this disclosure in its as-synthesized or synthetic form, and thus includes the structure directing agent (Q), but is not intended to be a solo representation of such material. The zeolite may contain impurities in its as-synthesized (or synthesized or synthetic) form, such impurities not being accounted for in formula III. Furthermore, Formula III does not include any charge or hydrogen (or proton) compensating ions that may be present in the as-synthesized zeolite.

[0035] The variable m is the molar ratio that represents the relationship of X2O3:YO2 (or X2O3 / YO2) in Formula III. In Formula III, the values ​​of the variable m are the same as those described in this disclosure for Formula II.

[0036] The variable n is a molar relationship that represents the Q:YO2 (or Q / YO2) relationship in Formula III. For example, n is 0.1 and the molar ratio of Q:YO2 (or Q / YO2) is 0.1. The molar ratio of Q:YO2 (or Q / YO2) may be from 0 to 0.5, for example, from 0.02 to 0.4, for example, from 0.05 to 0.3.

[0037] In a third embodiment, the present disclosure relates to a method for producing a zeolite, in particular a zeolite as defined in the first or second embodiment (e.g., EMM-70), comprising the following steps (a) to (d): (a) A process for preparing a synthesis mixture, the synthesis mixture comprising water, a source of an oxide of a tetravalent element (Y), a source of an oxide of a trivalent element (X), a structure directing agent (Q), optionally a source of hydroxide ions (OH), and optionally a source of alkali metal and / or alkaline earth metal elements (M); The structure directing agent (Q) has the following formula I: [ka] (Formula I) [In the formula, R is methyl or ethyl] and The molar ratio of Y / X in the synthesis mixture is less than 30; a step in which, when a source of fluoride (F) is present, the molar ratio of F / Y is less than 0.05; (b) heating the synthesis mixture under crystallization conditions comprising a temperature of 100°C to 200°C for a time period sufficient to form zeolite crystals; (c) recovering at least a portion of the zeolite from step (b); and (d) Optionally, treating the zeolite recovered in step (c) to remove at least a portion of the structure directing agent (Q).

[0038] The structure directing agent (Q) comprises at least one cation selected from the group consisting of 1,2,3-trimethyl-4,5,6,7-tetrahydrobenzimidazolium cation, 2-ethyl-1,3-dimethyl-4,5,6,7-tetrahydrobenzimidazolium cation, and mixtures thereof. The structure directing agent (Q) may be present in any suitable form, for example a halide (such as a fluoride, chloride, iodide or bromide), for example a hydroxide, or for example a nitrate. The structure directing agent (Q) may be present, for example, in the form of its hydroxide. A structure directing agent (Q) may be present in the synthesis mixture. In this case, the molar ratio of Q / Y may be 0.05 to 1.0. For example, it may be at least 0.1, or at least 0.15, or at least 0.2, up to 0.8, or up to 0.7, or up to 0.6. In this case, the molar ratio of Q / Y may be, for example, 0.1 to 0.8, or 0.15 to 0.5, for example, 0.2 to 0.4.

[0039] The synthesis mixture includes at least one source of an oxide of a tetravalent element Y (e.g., Si and / or Ge). Preferably, Y includes Si. More preferably, Y is Si. Suitable sources of tetravalent element Y that can be used to prepare (or manufacture) the synthesis mixture depend on the element Y selected. In embodiments where Y is silicon, suitable sources of Si (e.g., sources of silicon oxide) for use in the process include silicates, such as tetraalkylorthosilicates, e.g., tetramethylorthosilicate (TMOS) and tetraethylorthosilicate (TEOS), fumed silicas, such as Aerosil® (available from Evonik), Cabosperse® (available from Cabot), and Cabosil® (available from DMS), precipitated silicas such as Ultrasil® and Sipernat® 340 (available from Evonik), alkali metal silicates such as potassium silicate and sodium silicate, aqueous colloidal suspensions of silica such as those sold under the trade name Ludox® by EI du Pont de Nemours or those sold under the trade name Aerodisp® by Evonik. Preferred are silicates (or silicate salts), fumed silica, precipitated silica (or precipitated silica), alkali metal silicates (or alkali metal silicates) and colloidal silica (or colloidal silica or colloidal silica). In embodiments where Y is germanium, suitable sources of Ge include germanium oxide (or germanium oxide).

[0040] The synthesis mixture includes at least one source of an oxide of a trivalent element X (e.g., Al and / or B). Preferably, X includes Al and / or B, e.g., Al. More preferably, X is Al and / or B, e.g., Al. Suitable sources of trivalent element X that can be used to prepare (or manufacture) the synthesis mixture depend on the element X selected. In embodiments where X is aluminum, suitable sources of Al (e.g., sources of aluminum oxide (or aluminum oxide)) for use in the process include aluminum salts, particularly water soluble salts such as aluminum sulfate (or aluminum sulfate), aluminum nitrate (or aluminum nitrate), aluminum hydroxide (or aluminum hydroxide), alkali metal aluminates (or alkali metal aluminates), such as sodium aluminate (or sodium aluminate), and aluminum alkoxides, such as aluminum isopropoxide, as well as hydrated aluminum hydroxides (or aluminum oxides), such as boehmite, gibbsite, and pseudoboehmite, and mixtures thereof. Other sources of aluminum include, but are not limited to, other water soluble aluminum salts, sodium aluminate (or sodium aluminate), aluminum alkoxides, e.g., aluminum isopropoxide, or aluminum metal, e.g., aluminum in the form of chips. Particularly suitable sources of alumina are water-soluble salts such as aluminum sulfate, aluminum nitrate, aluminum hydroxide, and alkali metal aluminates (or alkali metal aluminates), such as sodium aluminate (or sodium aluminate) and potassium aluminate (or potassium aluminate). In embodiments where X is boron, suitable sources of B include boric acid and borate salts, such as sodium tetraborate (or sodium tetraborate) or borax and potassium tetraborate (or potassium tetraborate). Boron sources tend to be more soluble in hydroxide-mediated synthesis systems compared to aluminum sources.

[0041] Also, as an alternative or in addition to the sources of Y and X mentioned above, a source containing both elements Y and X can be used (e.g., a source of Si and Al). Examples of suitable sources containing both Si and Al elements include amorphous silica-alumina gels or dried silica-alumina powders, silica-aluminas, clays such as kaolin, metakaolin and zeolites, particularly aluminosilicates such as synthetic faujasite, and ultrastable faujasites such as Ultrastable Y (USY), Beta or other large to medium pore zeolites.

[0042] The molar ratio of Y / X in the synthesis mixture may be from 1 to less than 30, such as from 5 to 25, for example, 5 or from 10 to 20, for example, 15.

[0043] In a preferred embodiment, Y is Si, X is Al and the zeolite is an aluminosilicate. In another preferred embodiment, Y is Si, X is B and the zeolite is a borosilicate.

[0044] Optionally, the synthesis mixture may include one or more sources of alkali metal or alkaline earth metal cations (M). M is preferably selected from the group consisting of sodium, potassium, lithium, rubidium, calcium, magnesium, and mixtures thereof, preferably sodium and / or potassium, more preferably sodium. The source of sodium, if present, may be sodium hydroxide, sodium aluminate, sodium silicate, sodium aluminate or a sodium salt, for example, NaCl, NaBr or sodium nitrate. The source of potassium, if present, may be potassium hydroxide, potassium aluminate, potassium silicate, a potassium salt, such as KCl or KBr, or potassium nitrate. The source of lithium, if present, may be lithium hydroxide or a lithium salt, such as LiCl, LiBr, LiI, lithium nitrate or lithium sulfate. The source of rubidium, if present, may be rubidium hydroxide (or rubidium hydroxide) or a rubidium salt, such as RbCl, RbBr, RbI, or rubidium nitrate (or rubidium nitrate). The source of calcium, if present, may be, for example, calcium hydroxide. The source of magnesium, if present, may be, for example, magnesium hydroxide. The alkali metal or alkaline earth metal cation M may also be present in one or more sources of trivalent element X (e.g. sodium aluminate, sodium tetraborate, potassium tetraborate) and / or one or more sources of tetravalent element Y (e.g. potassium silicate and / or sodium silicate). The synthesis mixture may include a source of alkali metal or alkaline earth metal cations (M). In this case, the molar ratio of M / Y may be from 0 to 1.0, for example, from 0.05 to 0.5, for example, from 0.05 to less than 0.1. Alternatively, the synthesis mixture may be substantially free of (or substantially free of) alkali metal or alkaline earth metal cations (M).

[0045] Optionally, the synthesis mixture may also include at least one source of hydroxide ions (OH). For example, hydroxide ions may be present as counter ions to the structure directing agent (Q), or may be present by using aluminum hydroxide as the source of Al. Also, a suitable source of hydroxide ions may be selected from the group consisting of alkali metal hydroxides, alkaline earth metal hydroxides, ammonium hydroxide, and mixtures thereof: for example, sodium hydroxide, potassium hydroxide, lithium hydroxide, rubidium hydroxide, calcium hydroxide, magnesium hydroxide, ammonium hydroxide, and mixtures thereof; more frequently, sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonium hydroxide, and mixtures thereof; most frequently, sodium hydroxide and / or potassium hydroxide. The synthesis mixture may comprise a source of hydroxide ions, the molar ratio of OH / Y being from 0 to 1.0, such as from 0.05 to 0.8, for example from 0.1 to 0.6 or from 0.15 to 0.5, for example from 0.2 to 0.5. Alternatively, the synthesis mixture may be substantially free of (or substantially free of) hydroxide sources.

[0046] The synthesis mixture used to prepare the EMM-70 material contains fluoride ions (F) and the molar ratio of F / Si is less than 0.05, for example, 0 to less than 0.04, or 0 to 0.02, or 0 to 0.01, for example, 0. In particular, the synthesis mixture used to prepare (or manufacture) the EMM-70 zeolite is substantially free of (or substantially free of) fluoride ions (F). This means that no source of fluoride ions is added to the synthesis mixture in any substantial amount, for example, the F / Si molar ratio of the synthesis mixture may be less than 0.05, e.g., less than 0.02, less than 0.01, or less than 0.005, e.g., 0. Fluoride ions (F), if present, in the synthetic mixture of molecular sieves may originate from any compound capable of releasing fluoride ions (e.g., hydrogen fluoride (HF)); salts (e.g., metal fluorides) containing one or several fluoride ions (preferably where the metal is sodium, potassium, calcium, magnesium, strontium or barium); ammonium fluoride (NH4F); and ammonium bifluoride (NH4HF2). Small amounts of fluoride ions (F) may also be present as impurities, for example in any source of alkali metal or alkaline earth metal cations (M).

[0047] The synthesis mixture may optionally further comprise at least one source of halide ions (W), which are different from fluoride ions and may be selected from the group consisting of chloride, bromide or iodide. The source of halide ions (W) may be any compound capable of releasing halide ions in the molecular sieve synthesis mixture. For example, a halide ion can be present as a counter ion (or counter ion) of the structure directing agent (Q). Non-limiting examples of sources of halide ions include hydrogen chloride, ammonium chloride, hydrogen bromide, ammonium bromide, hydrogen iodide and ammonium iodide; salts containing one or several halide ions, such as metal halides, preferably those in which the metal is sodium, potassium, calcium, magnesium, strontium or barium; ammonium halides; or tetraalkylammonium halides, such as tetramethylammonium halide or tetraethylammonium halide. Small amounts of halide ions (W) may also be present as impurities, for example in any source of alkali metal or alkaline earth metal cations (M). Halide ions (W) may be present in a molar ratio W / Y of from 0 to 0.2, such as from 0 to 0.1, such as less than 0.1 or even 0. In a preferred embodiment, the synthesis mixture may be substantially free of (or substantially free of) halide ions (W).

[0048] The synthesis may be carried out with or without the addition of nucleating seeds. When nucleation seeds are added to the synthesis mixture, the seeds (or seed crystals) may have the same structure or a different structure from the zeolite of the present disclosure, or the EMM-70 material, from conventional synthesis, and may be suitably present in an amount of about 0.01 ppm to about 10,000 ppm by weight based on the synthesis mixture, for example, about 100 ppm to about 5,000 ppm by weight of the synthesis mixture.

[0049] The synthesis mixture typically contains water in a molar ratio of H2O / Y=1-100, such as 10-80 or 15-50, such as 20-40, for example 25 or 30. Depending on the nature of the components contained in the base mixture, a certain amount of solvent (e.g. water from the hydroxide solution and, if necessary, methanol and ethanol from the hydrolysis of the silica source) contained in the base mixture may be removed to achieve the desired solvent / Y molar ratio in the synthesis mixture. Suitable methods for reducing the solvent content may include evaporation under a static or dynamic atmosphere (e.g., ambient air, dry nitrogen, dry air), or by spray drying or freeze drying. Water may be added to the resulting mixture to achieve the desired H2O / Y molar ratio (if too much water is removed during the solvent removal process (or step or method)). In some instances, removal of water is not necessary (if the preparation has a sufficient H2O / Y molar ratio).

[0050] Carbon (in the form of CH2) may be present in various sources of components used to prepare the zeolites of the present disclosure (e.g., tetravalent (silica) or trivalent (alumina) elements) and is incorporated into the zeolite framework as a bridging atom. The nitrogen atoms may be incorporated as bridging atoms into the framework of the zeolite framework (after the SDA has been removed).

[0051] In one or more embodiments, the synthesis mixture after solvent adjustment (e.g., when the desired water:silica ratio is achieved) may be mixed by a mechanical process, such as by stirring or high shear blending to ensure proper homogenization of the base mixture. For example, dual asymmetric centrifugal mixing (e.g., a FlackTek Speed ​​Mixer) may be used (mixing speed is 1,000-3,000 rpm (e.g., 2000 rpm)).

[0052] The synthesis mixture is then subjected to suitable crystallization conditions to form a zeolite. Zeolite crystallization may be carried out under static or dynamic (or stirred) conditions in a suitable reaction vessel (e.g., a Teflon-lined or stainless steel autoclave placed in a convection oven maintained at a suitable temperature).

[0053] The crystallization in step (b) of the process is typically carried out at a temperature between 100° C. and 200° C., for example between 150° C. and 170° C., for a period of time which is sufficient for crystallization to occur at the temperature employed. For example, at higher temperatures, crystallization time may be less. For example, the crystallization conditions in process (or step) (b) of the method may comprise heating for a period of from 1 day to 100 days, such as from 1 day to 50 days, for example from 10 days or from 20 days to 40 days. The time of crystallization may be established by methods known in the art, such as by sampling the synthesis mixture at various times (or occasions), determining the yield of precipitated solids, and determining the degree of crystallinity (or crystallinity) of the precipitated solids by X-ray. Unless otherwise stated in this disclosure, the temperature measured is the temperature of the environment surrounding the material being heated (eg, the temperature of the atmosphere in which the material is heated).

[0054] Typically, the zeolite is formed (or produced) in solution and can be recovered by standard means (eg, by centrifugation or filtration). The separated zeolite may also be washed, recovered by centrifugation or filtration, and dried.

[0055] The zeolites of the present disclosure may be at least partially dehydrated (e.g., dried) when employed as adsorbents (or adsorbents or adsorbents) or as catalysts in processes (or steps or methods) for the conversion (or transformation or conversion) of organic compounds. The dehydration can be carried out, for example, by heating to a temperature within a range of 80°C to 500°C, for example, 90°C to 370°C, for 30 minutes to 48 hours at atmospheric pressure, subatmospheric pressure, or superatmospheric pressure in an atmosphere of air, nitrogen, or the like. Alternatively, dehydration can be performed at room temperature by simply placing the molecular sieves under reduced pressure, but longer times are required to obtain a sufficient amount of dehydration.

[0056] As a result of the crystallization process, the recovered product contains within its pores at least a portion of the structure directing agent used in the synthesis. Thus, the as-synthesized zeolite recovered from process (c) may be subjected to a heat or other treatment to remove some or all of the SDA introduced into the pores during synthesis. Thermal treatment (e.g., calcination) of the as-synthesized zeolite typically involves exposing the material to high temperatures in a furnace in an atmosphere selected from air, nitrogen, ozone, or mixtures thereof to sufficiently remove some or all of the SDA. Although subatmospheric pressures may be used in this heat treatment, atmospheric pressure is preferred for simplicity. The heat treatment may be carried out at a temperature of up to 925°C, for example, between 300°C and 700°C, or between 400°C and 600°C. The temperature measured is the temperature of the surrounding environment of the sample (or specimen). Heat treatment (e.g. calcination) may be carried out in a box furnace (dry air), which is exposed to a drying tube containing a desiccant that removes water from the air. Heating is usually for calcination (or calcination) for at least one minute, and generally for up to a day, or up to a few days. Heating may be performed first under a nitrogen atmosphere, and then the atmosphere may be switched to air and / or ozone.

[0057] The zeolite may also be subjected to an ion exchange treatment (e.g., with aqueous ammonium salts such as ammonium nitrate, ammonium chloride, and ammonium acetate) in order to remove any remaining alkali metal and / or alkaline earth metal cations and replace them with protons, thereby producing the acid form of the molecular sieve. To the extent desired, original cations of the as-synthesized material (e.g., alkali metal cations) can be replaced with other cations by ion exchange. Preferred replacement cations include hydrogen ions, hydrogen precursors (or hydrogen precursors) such as ammonium ions, and mixtures thereof. The as-made molecular sieves may be dried prior to the ion exchange process (or step). The ion exchange step (or steps) may be carried out before or after the calcination (or calcination) step (or steps).

[0058] Optionally, in embodiments where the zeolite contains boron atoms, for example when the zeolite is a borosilicate, aluminum atoms may be introduced into the zeolite framework during an exchange process following a hydrothermal synthesis reaction (in which some or all of the SDA has been removed). Such an exchange process may include exposing the zeolite to a source (or process or step) of aluminum (eg, an aqueous solution containing an aluminum salt). Such an exchange process (or step or method) may include exposing the zeolite to conditions (or steps or processes) sufficient to exchange at least a portion, and up to substantially all, of the boron atoms (or boron atoms) in the framework silicates with aluminum atoms. For example, calcined borosilicate zeolites can be converted to aluminosilicates by heating the boron-containing zeolite (after calcination) with a solution of aluminum sulfate, aluminum nitrate, aluminum chloride and / or aluminum acetate (e.g., in a sealed autoclave in a convection oven at 100°C or boiling temperature (open system)). The aluminium treated zeolite may then be recovered by filtration and washed with deionised water.

[0059] The zeolite may also be subjected to other treatments (eg, steaming and / or washing with a solvent). Such treatments are well known to those skilled in the art and are carried out to modify the properties of the molecular sieve as desired.

[0060] The zeolites of the present disclosure, when some or all of the SDA has been removed, may be used as catalysts or catalyst supports or as adsorbents in the conversion of a wide variety of hydrocarbons, such as the conversion of organic compounds to conversion products.

[0061] The zeolites of the present disclosure (when some or all of the SDA has been removed) may be used as adsorbents (e.g., adsorbents for separating at least one component from a mixture of components in a gas or liquid phase having differential adsorption characteristics with respect to a material). Thus, with respect to zeolites, at least one component may be partially or substantially completely separated from a mixture of components having differential adsorption properties by contacting the mixture with the zeolite, thereby selectively adsorbing (or absorbing) one component. For example, in a process for selectively separating one or more desired components of a feedstock from the remaining components of the feedstock, the feedstock may be contacted with an adsorbent comprising a zeolite of the present disclosure under effective adsorption conditions, thereby forming an adsorbed product and an effluent product. One or more desired constituents (or components) are recovered from the adsorbed (or absorbed) product or from the effluent product (or product).

[0062] Additionally, the zeolites of the present disclosure (when some or all of the SDA has been removed) may be used as catalysts to catalyze a wide variety of organic compound conversion processes. Examples of chemical conversion processes that may be effectively catalyzed by the zeolites described herein include those that require acid-active catalysts, either alone or in combination with one or more other catalytically active substances, including other crystalline catalysts. Examples of organic conversion processes that may be catalyzed by the zeolites described in this disclosure include cracking (or cracking), hydrocracking (or hydrocracking), isomerization (or isomerization), polymerization (or polymerization), reforming (or reforming), hydrogenation (or hydrogenation), dehydrogenation (or dehydrogenation), dewaxing (or dewaxing), hydrodewaxing (or hydrodewaxing), adsorption (or adsorption), alkylation (or alkylation), transalkylation (or transalkylation), dealkylation (or dealkylation), hydrodesilylation, hydrodesilylating ... (or hydrodecylization), disproportionation, oligomerization, dehydrocyclization / cracking, hydrocracking, isomerization, polymerization, reforming, hydrogenation, dehydrogenation, dewaxing, hydrodewaxing, adsorption, alkylation, alkylation,transalkylation (or transalkylation), dealkylation (or dealkylation), hydrodesilylation (or hydrodecylation), disproportionation (or disproportionation), oligomerization (or oligomerization, dehydrocyclization, conversion of methanol to olefins), deNOx, x (deNOx) uses (or adaptations or adaptations or applications) and combinations thereof. The conversion of the hydrocarbon feed (or feed) may be carried out in any convenient mode, for example in a fluidized bed, moving bed or fixed bed reactor, depending on the type of process (or step or method) desired.

[0063] The zeolites of the present disclosure may be formulated into product compositions by combination with other materials, such as binders and / or matrix materials (which impart additional hardness to the final product). Such other materials may be inert or may be catalytically active materials.

[0064] For example, it may be desirable to incorporate another material into the zeolites of the present disclosure of the present invention that is resistant to the temperatures and other conditions employed during use. Such materials include synthetic or natural zeolites as well as inorganic materials such as clays, silica and / or metal oxides (e.g., alumina) and mixtures thereof. The metal oxides (or metal oxides) may be naturally occurring or in the form of gelatinous precipitates or gels (including mixtures of silica and metal oxides). The use of resistant materials (i.e., combined with the zeolites of the present disclosure or present during the synthesis of the zeolites as-made) in conjunction with the zeolites of the present disclosure (the crystals of which are active) tends to change the selectivity and / or conversion of the catalyst in a particular organic conversion process. An inert resistant material is suitably useful as a diluent to control the amount of conversion in a given process, so that a product can be obtained in an economical and orderly manner without employing other means to control the rate of reaction. These materials may be incorporated into naturally occurring clays (eg, bentonite and kaolin). The breaking strength (or crush strength) of a product (or article or product) can be improved (or enhanced) under commercial (or market) operating conditions. The above inert resistant materials, i.e. clays, oxides, etc., function as binders for the catalyst. A catalyst having good crush strength can be beneficial because in commercial use it is desirable to prevent the catalyst from breaking down into powder-like material.

[0065] Natural clays that can be used include the montmorillonite and kaolin families, including subbentonites (or subbentonites), and kaolins (such as those commonly known as Dixie, McNamee, Georgia, and Florida clays), where the major inorganic constituents are halloysite, kaolinite, dickite, nacrite, or anauxite. Such clays can be used in the raw state in which they were originally mined, or after being subjected to calcination, acid treatment or chemical modification. Binders useful in compositions with the zeolites of the present disclosure also include inorganic oxides selected from silica, zirconia, titania, magnesia, beryllia, alumina, yttria, gallium oxide, zinc oxide, and mixtures thereof.

[0066] In addition to the materials described above, the zeolites of the present disclosure may be blended with porous matrix materials (e.g., silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, and ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia).

[0067] These binder materials are resistant to temperature and other conditions, such as mechanical attrition, that occur during the various hydrocarbon separation processes. Thus, the zeolites of the present disclosure can be used in extrudate form (or foam) with a binder. These are typically joined (or bonded or bonded) by forming (or producing) a tablet (or pill), sphere (or sphere) or extrudate (or extrudate or extrude). The extrudates (or extrudates or extrudes) are typically formed (or produced) by extruding molecular sieves, optionally in the presence of a binder, followed by drying and calcination (or calcination) of the resulting extrudates (or extrudates or extrudes). Further treatment (eg, steaming) and / or ion exchange may be performed as required. The molecular sieve may be optionally bound (or bonded) to a binder. The binder has a surface area of ​​at least 100 m 2 / g, e.g., at least 200m2 / g, if necessary, at least 300m 2 / g.

[0068] The relative proportions of the molecular sieve and inorganic oxide matrix may vary widely, with the molecular sieve content being in the range of about 1 to about 100% by weight, more usually in the range of about 2 to about 95% by weight, optionally in the range of about 20 to about 90% by weight, based on the composite, particularly when such composite is prepared in extrudate form.

[0069] The zeolites of the present disclosure may also be used in intimate combination with a hydrogenation component (e.g., tungsten, vanadium, molybdenum, rhenium, nickel, cobalt, chromium, manganese, or a precious metal (e.g., platinum or palladium)) in which a hydrogenation-dehydrogenation function may be performed. Such hydrogenation components may be incorporated into the composition by one or more of the following processes: cocrystallization (the composition is exchanged to the extent that an element of group IIIA (e.g., aluminum) is present in the structure), or It is intimately physically mixed (or blended) with such hydrogenation components. Such hydrogenation components can also be impregnated into or onto the zeolite, for example by treating the molecular sieve with hydrogenation metal-containing ions. For example, in the case of palladium, suitable palladium compounds for this purpose include a variety of compounds including chloroplatinic acid, platinum chloride, and platinum amine complexes. Also, combinations of metals and methods for their introduction can be used.

[0070] One of ordinary skill in the art will appreciate that the zeolites of the present disclosure may contain impurities (e.g., amorphous materials, unit cells having different topologies (e.g., molecular sieves or quartz having different framework types) that may or may not affect the performance of the resulting catalyst) and / or other impurities (e.g., heavy metals and / or organic hydrocarbons). The molecular structure of the zeolites disclosed herein may be characterized by different framework types. Typical examples of sieves are, for example, molecular sieves with the framework types FAU or IWV (eg faujasite and ITQ-27). The zeolites of the present disclosure are preferably substantially free of impurities. The term "substantially free of impurities" (or the alternative term "substantially pure"), as used herein, means that the zeolite has a small or minor proportion (less than 50% by weight) of such impurities (e.g., "non-EMM-70 materials"). Such impurities are preferably less than 20% by weight, more preferably less than 10% by weight, even more preferably less than 5% by weight, and most preferably less than 1% by weight (e.g., less than 0.5% by weight or less than 0.1% by weight). Such weight percent (wt%) values ​​are based on the combined weight of impurities and pure zeolite. The amount of impurities can be suitably determined by powder XRD, rotational electron diffraction and / or SEM / TEM (eg, different crystal morphologies).

[0071] The zeolites described in this disclosure are substantially crystalline (or crystalline or crystal or crystalline). The term "crystalline" as used herein means that a material is in a crystalline solid form, including, but not limited to, single-component or multi-component crystalline forms (e.g., solvates, hydrates, and co-crystals). Crystalline (or crystalline or crystal or crystalline) can mean having a regular repetition of molecules and / or an orderly arrangement of molecules and having a distinct crystal lattice. For example, the zeolites may differ in their water or solvent content. The lattices of different crystalline materials can be identified by characterization methods in the solid state, such as XRD (e.g., powder XRD). Other characterization methods known to those of skill in the art can further aid in the identification of the crystalline form and can further aid in the determination of stability and solvent / water content. The term "substantially crystalline" as used in this disclosure means that the majority (50% or more by weight) of a sample of the material being described is in crystalline form, with the remainder of the sample being in a non-crystalline form (amorphous form or non-crystalline form). In one or more embodiments, a substantially crystalline sample has at least 95% crystallinity (e.g., 5% is in non-crystalline form); having at least 96% crystallinity (e.g., 4% is in a non-crystalline form); having at least 97% crystallinity (e.g., 3% is in a non-crystalline form); having at least 98% crystallinity (e.g., about 2% is in a non-crystalline form); having at least 99% crystallinity (e.g., 1% is in a non-crystalline form); It has a crystallinity of 100% (eg, 0% is a non-crystalline form).

[0072] Aspects of the present disclosure will now be described in further detail by way of specific examples. The following examples are offered for illustrative purposes and are not intended to limit (or restrict) the present disclosure in any way (or manner). Those skilled in the art will readily understand that the various parameters can be changed or modified while still achieving essentially the same results. EXAMPLES

[0073] (Example) The present invention is further described below, but is not limited to the scope thereof.

[0074] In these examples, X-ray diffraction (XRD) patterns of the as-synthesized and as-calcined materials were recorded (2θ range, 2-50°) using an X-Ray Powder Diffractometer (Bruker DaVinci D8 Discovery instrument), continuous mode (CuKα radiation), Bragg-Bentano geometry (with a Vantec 500 detector). The interplanar spacing (d-spacing) was calculated in Angstroms, and the relative intensity of the line (I / Io) is the ratio of the peak intensity of the longest line (above background) to the peak intensity of the longest line (above background). These intensities remain uncorrected (or uncalibrated) for the Lorentz effect and the polarization effects. The positions (locations) of the diffraction peaks (2θ) and the relative peak area intensities (I / I(o)) of the lines (where I(o) is the intensity (above background) of the longest line (or ray)) were determined (using the MDI Jade peak search algorithm). It should be understood that diffraction data listed as a single line may consist of multiple overlapping lines. Under certain conditions (e.g., differences in crystallographic changes), these lines may appear resolved or partially resolved. Typically, such crystallographic changes may involve minor changes in unit cell parameters and / or changes in crystal symmetry, without altering framework connectivity. Additionally, such minor effects (including changes in relative intensity) may result from differences in cation content, framework composition, the nature and degree of pore filling, crystal size and shape, preferred orientation, and thermal and / or hydrothermal history.

[0075] Scanning electron microscopy (SEM) images were obtained of the as-synthesized materials (Hitachi 4800 Scanning Electron Microscope). SEM images were used to aid in the assessment of product purity. The presence of distinctly different crystal morphologies in SEM images can indicate impurities in the form of other crystalline materials. Such approximate analysis may be particularly useful in recognizing (or identifying) the presence of relatively small amounts of crystalline impurity formation, even if such presence is not discernible (or discernible or identifiable or unidentifiable) from the XRD pattern of the product.

[0076] The total BET surface area (or Overall BET Surface Area) of a material (S BET) was determined by the BET method, as described in S. Brunauer et al., (1938), J. Am. Chem. Soc., v. 60, pg. 309, which is incorporated herein by reference, and utilizes nitrogen adsorption-desorption (or desorption) at liquid nitrogen temperatures. The external surface area (S) of a material ext ) was obtained from the t-plot method. The micropore surface area (S) of a material micro ) to the total BET surface area (S BET ) to the external surface area (S ext ) was calculated by subtracting

[0077] The micropore volume (or micropore volume or micropore volume) of a material (V micro ) can be determined using methods known in the relevant art. For example, the pore volume of a material can be measured by nitrogen physical adsorption. The data can be analyzed by the t-plot method, which is described in Lippens, BC et al., (1965), "Studies on pore system in catalysts: V. The t method," J. Catal., v.4, pg. 319, which describes the micropore volume method and is incorporated herein by reference.

[0078] The molar ratios and conditions used in the synthesis of Examples 2-7 and the resulting products are described in detail below and summarized in Table 3.

[0079] Example 1a Synthesis of 1,2,3-trimethyl-4,5,6,7-tetrahydro-1H-benzo[d]imidazol-3-ium cation (SDA-1) 2-Methyl-4,5,6,7-tetrahydro-1H-benzimidazole 40 g of 2-methylbenzimidazole was dissolved in 320 ml of glacial acid. 15 g of palladium (10% by weight on carbon) were added and the reaction mixture was treated with hydrogen (temperature of 120° C., pressure of 80 bar, for 24 hours). The solution was filtered through Celite and washed with glacial acid. The solvent was evaporated under reduced pressure, then a solution of sodium hydroxide was added to bring the pH of the solution to 9-10. The precipitate was filtered, washed with water, then dissolved in chloroform and extracted with a solution of saturated sodium chloride. The organic phase was dried over sodium sulfate, filtered and concentrated under reduced pressure.

[0080] 1,2,3-Trimethyl-4,5,6,7-tetrahydro-1H-benzo[d]imidazol-3-ium iodide 13.6 g of 2-methyl-4,5,6,7-tetrahydro-1H-benzimidazole, 70 g of iodomethane, and 27 g of potassium carbonate were added to 150 ml of acetonitrile (CH3CN) in a 250 mL round bottom flask equipped with a magnetic stir bar. The suspension was then refluxed for 18 hours and then cooled to room temperature. The solution was then filtered using a Buchner funnel, and the filtrate was concentrated on a rotovap. Dichloromethane was added to the concentrate to remove residual potassium salts. The filtrate (in dichloromethane) was concentrated on a rotovap and dried under reduced pressure to give 1,2,3-trimethyl-4,5,6,7-tetrahydro-1H-benzo[d]imidazol-3-ium iodide.

[0081] 1,2,3-Trimethyl-4,5,6,7-tetrahydro-1H-benzo[d]imidazol-3-ium hydroxide The iodide salt was converted to the hydroxide form by ion exchange (ion exchange resin Amberlite® IRN78 OH hydroxide form (iodide:resin:water ratio=1:3.5:5)). The exchange was carried out at room temperature overnight.

[0082] Example 1b Synthesis of 2-ethyl-1,3-dimethyl-4,5,6,7-tetrahydro-1H-benzo[d]imidazol-3-ium cation (SDA-2) The three step process of Example 1a was followed except that 2-methylbenzimidazole was replaced with 2-ethylbenzimidazole.

[0083] Example 2: SDA-1, USY zeolite, Si / Al=15 The following reagents were mixed together in the PTFE liner of a 23 mL Steel Parr autoclave: 2.87 g of SDA-1 solution (13.9 wt%), 0.72 g of NaOH solution (4 wt%), 2.16 g deionized water, and 0.190g of Ultrastable Y (USY) zeolite (Si / Al molar ratio=15 (available from Zeolyst as CBV720)) The synthesis mixture produced had the following composition, in terms of molar ratios: 25H2O:1SiO2:0.033Al2O3:0.23QOH:0.07NaOH

[0084] The liner was then capped and sealed in a 23 mL Parr autoclave and placed on a spit in a convection oven. The reactor was heated (160° C., tumbling conditions (approximately 30 rpm) for 6 weeks). The product was isolated by filtration, rinsed with deionized water and dried. The as-synthesized material was then calcined (to 580° C. in air, box furnace, ramp rate = 3° C. / min). The temperature was maintained at 580° C. for 8 hours, and then the box furnace was allowed to cool.

[0085] XRD analysis of the as-synthesized and as-calcined materials showed that the materials may have similar powder XRD patterns, in terms of 2θ (°) and d-spacing, for the as-synthesized and as-calcined SSZ-64, respectively. However, the relative intensities were different (as shown in Tables I / IA and II / IIA of WO2004 / 013042A1). Such a new product was identified as EMM-70. FIG. 1 shows an SEM image of the product in the as-synthesized state. The exact structure of EMM-70 is unknown.

[0086] The micropore surface area (S) of the EMM-70 material in its as-calcined or calcined version micro ) is 505m 2 / g. Its external surface area (S ext ) is 63m 2 / g. Its micropore volume (or micropore volume or micropore volume or micropore volume) (V micro ) was 0.18cc / g.

[0087] Example 3 SDA-1, USY zeolite, Si / Al=15 Example 3 was carried out under the same conditions as Example 2. However, the synthesis mixture contained more SDA-1 and less NaOH. As a result, the composition in terms of molar ratio was as follows: 25H2O:1SiO2:0.033Al2O3:0.40QOH:0.05NaOH

[0088] After heating at 160° C. for 4 weeks, a pure EMM-70 product was obtained (as identified by its XDR pattern).

[0089] Comparative Example 4: SDA-1, USY zeolite, Si / Al=30 Comparative Example 4 was carried out under the same conditions as in Example 1. However, as a source of Si and Al, USY zeolite (Si / Al molar ratio=30) (available from Zeolyst as CBV760) was used, so that in the synthesis mixture, the Si / Al molar ratio=30. After heating at 160° C. for 4 weeks, no EMM-70 was obtained. The resulting product was identified based on its XRD pattern as ITQ-27, as disclosed in JE Schmidt et al., (2016), Chem. Eur. J., v.22, pp. 4022-4029 or WO2006 / 055305A2.

[0090] Example 5 SDA-2, USY zeolite, Si / Al=15 Example 5 was carried out under the same conditions as Example 1. However, SDA-1 was replaced with SDA-2, where the molar ratio of Q / Si=0.25 (instead of 0.23). After heating at 160° C. for 4 weeks, a pure EMM-70 product was obtained (as identified by its XDR pattern). 2 and 3 show the powder XRD patterns of the as-synthesized and as-calcined products of Example 5. Tables 4 and 5 below list the peaks and intensities of the as-synthesized and as-calcined EMM-70 products of Example 5. FIG. 4 shows an SEM image of the as-synthesized product of Example 5.

[0091] Example 6 SDA-2, USY zeolite, Si / Al=15 Example 6 was carried out under the same conditions as Example 5. However, the synthesis mixtures contained various amounts of SDA-2, NaOH, and water, so that, in terms of molar ratios, the compositions were as follows: 30H2O:1SiO2:0.033Al2O3:0.20QOH:0.10NaOH

[0092] After heating at 160° C. for 5 weeks, a product of EMM-70 was obtained (along with a small amount of ITQ-27) (as identified by its XDR pattern).

[0093] Example 7 SDA-2, colloidal silica, sodium aluminate, Si / Al=15 Example 7 was carried out under the same conditions as Example 6. However, Ludox HS40 (40 wt% colloidal silica suspension) was used as the source of Si, sodium aluminate (NaAlO2, 25 wt% Al2O3, 19.3 wt% Na2O) was used as the source of Al, and NaOH was present at a slightly larger Na / Si molar ratio of 0.15. After heating at 160° C. for 5 weeks, a product of EMM-70 was obtained (along with a small amount of ITQ-27) (as identified by its XDR pattern).

[0094] Example 8 SDA-2, USY zeolite, Si / Al=15 Example 8 was carried out under the same conditions as Example 5. However, the synthesis mixture contained a higher amount of SDA-2 and was carried out in the absence of NaOH, so that the composition (or composition or condition), in terms of molar ratios, was as follows: 25H2O:1SiO2:0.033Al2O3:0.35QOH

[0095] After heating at 160° C. for 3 weeks, a product of EMM-70 was obtained (with an insoluble faujasite zeolite phase) (as identified by its XDR pattern).

[0096] [Table 7]

[0097] * SDA-1 = 1,2,3-trimethyl-4,5,6,7-tetrahydro-1H-benzo[d]imidazol-3-ium cation **SDA-2 = 2-ethyl-1,3-dimethyl-4,5,6,7-tetrahydro-1H-benzo[d]imidazol-3-ium cation

[0098] [Table 8]

[0099] [Table 9]

[0100] While the present invention has been described and illustrated with reference to specific embodiments, it will be understood by those skilled in the art that the present invention is susceptible to many different alterations, modifications and variations thereon that are not specifically set forth in the present disclosure. Furthermore, when a lower limit and an upper limit of a numerical value are described in the present disclosure, it will be apparent to a person skilled in the art that a range from any lower limit to any upper limit is also contemplated. Additionally, all numerical values ​​set forth in the detailed description of the present disclosure are modified by "about" to indicate that the stated value takes into account experimental error and variations, and may be predicted (or expected) by one of ordinary skill in the art.

[0101] In the above description, wholes or elements are described which have known, obvious, or foreseeable equivalents (or equivalents), and such equivalents are then incorporated in this disclosure as if each was described. The following claims should be referenced to determine the true scope of the invention, which should be construed to encompass any such equivalents. It is also understood that any features or wholes of the invention described as being preferred, advantageous, convenient, or the like are optional for the reader and do not limit the scope of the independent claims. Further, it should be understood that while any such feature or features may be beneficial in some embodiments of the present invention, in other embodiments it may be undesirable and therefore may not be present.

[0102] Additionally or alternatively, the invention relates to the following embodiments:

[0103] EMBODIMENT 1 A zeolite, in its calcined form (or as-calcined form or calcined form or calcined form), having an X-ray diffraction pattern including the peaks set out in Table 1 or Table 1A.

[0104] EMBODIMENT 2 Formula II below: (m)X2O3:YO2 (formula II) [In the formula, 0.017 <m≦0.1であり、 X is a trivalent element, Y is a tetravalent element. 2. The zeolite of embodiment 1 having a molecular formula:

[0105] EMBODIMENT 3 X includes at least one of aluminum and boron; Preferably, X is selected from the group consisting of aluminum, boron, and combinations thereof; More preferably, X comprises or is aluminium. 3. A zeolite as defined in embodiment 2.

[0106] EMBODIMENT 4 Y includes at least one of silicon and germanium; Preferably, Y is selected from the group consisting of silicon, germanium, and combinations thereof; More preferably, Y comprises or is silicon. 4. A zeolite according to embodiment 2 or 3.

[0107] EMBODIMENT 5 A zeolite, in its as-synthesized form, having an X-ray diffraction pattern including the peaks set out in Table 2 or Table 2A.

[0108] EMBODIMENT 6 Formula III below: (q) Q:(m) X2O3:YO2 (Formula III) [In the formula, 0≦q≦0.5, 0.017 <m≦0.1であり、 Q is represented by the following formula I: [ka] (Formula I) [R is methyl or ethyl] and wherein the cation is selected from the group consisting of 4,5,6,7-tetrahydrobenzimidazolium cations X is a trivalent element, Y is a tetravalent element. 6. The zeolite of embodiment 5, having a molecular formula:

[0109] EMBODIMENT 7 X includes at least one of aluminum and boron; Preferably, X is selected from the group consisting of aluminum, boron, and combinations thereof; More preferably, X comprises or is aluminium. 7. A zeolite as defined in embodiment 6.

[0110] EMBODIMENT 8 Y includes at least one of silicon and germanium; Preferably, Y is selected from the group consisting of silicon, germanium, and combinations thereof; More preferably, Y comprises or is silicon. 8. A zeolite according to embodiment 6 or 7.

[0111] EMBODIMENT 9 8. The zeolite according to any one of embodiments 6 to 7, wherein the structure directing agent (Q) comprises at least one cation selected from the group consisting of 1,2,3-trimethyl-4,5,6,7-tetrahydrobenzimidazolium cation, 2-ethyl-1,3-dimethyl-4,5,6,7-tetrahydrobenzimidazolium cation, and mixtures thereof.

[0112] EMBODIMENT 10 The zeolite according to any one of the first to nine embodiments, which is an aluminosilicate or a borosilicate and has a molar ratio of Si / Al or Si / B of less than 30, preferably 5-25, more preferably 10-25.

[0113] EMBODIMENT 11 A method for producing the zeolite according to any one of embodiments 1 to 10, comprising the following steps (a) to (d): (a) A process for preparing a synthesis mixture comprising water, a source of an oxide of a tetravalent element (Y), a source of an oxide of a trivalent element (X), a structure directing agent (Q), optionally a source of hydroxide ions (OH), and optionally a source of alkali metal and / or alkaline earth metal elements (M), The structure directing agent (Q) has the following formula I: [ka] (Formula I) [In the formula, R is methyl or ethyl] and wherein the cation is selected from the group consisting of 4,5,6,7-tetrahydrobenzimidazolium cations the molar ratio of Y / X in the synthesis mixture is less than 30, and if a source of fluoride (F) is present, the molar ratio of F / Y is less than 0.05; (b) heating the synthesis mixture under crystallization conditions comprising a temperature of 100°C to 200°C for a time or period sufficient to form zeolite crystals; (c) recovering at least a portion of the zeolite from step (b); (d) Optionally, treating the zeolite recovered in step (c) to remove at least a portion of the structure directing agent (Q). A method comprising:

[0114] EMBODIMENT 12 12. The method of embodiment 11, wherein the structure directing agent (Q) comprises at least one cation selected from the group consisting of 1,2,3-trimethyl-4,5,6,7-tetrahydrobenzimidazolium cation, 2-ethyl-1,3-dimethyl-4,5,6,7-tetrahydrobenzimidazolium cation, and mixtures thereof.

[0115] EMBODIMENT 13 13. The method according to embodiment 11 or 12, wherein the structure directing agent (Q) is in the form of a halide, hydroxide or nitrate, preferably the structure directing agent (Q) is in the form of a hydroxide.

[0116] EMBODIMENT 14 The trivalent element X includes one or more of aluminum and boron; Preferably, X is selected from the group consisting of aluminum, boron, and combinations thereof; More preferably, X comprises or is aluminum; the tetravalent element Y includes one or more of silicon and germanium; Preferably, Y is selected from the group consisting of silicon, germanium, and combinations thereof; More preferably, Y comprises or is silicon. The method according to any one of claims 11 to 13.

[0117] EMBODIMENT 15 The synthesis mixture has the following molar ratio composition: [Table 10] The method according to any one of embodiments 11 to 14, comprising:

[0118] EMBODIMENT 16 16. The method according to any one of embodiments 11 to 15, wherein the synthesis mixture comprises a source of fluoride (F), and the molar ratio of F / Y is between 0 and 0.02, more preferably between 0 and 0.01, and most preferably the synthesis mixture is substantially free of fluoride (F) ions.

[0119] EMBODIMENT 17 11. A process (or method) for converting (or transforming or converting or converting) an organic compound into a conversion product (or conversion product or conversion product), the process (or method) comprising contacting (or contacting step or process) an organic compound with a zeolite according to any one of embodiments 1 to 10.

Claims

1. Zeolite, in its calcined form, exhibits the peaks shown in Table 1 below: 【Table 1】 The zeolite has an X-ray diffraction pattern comprising:

2. Formula II below: (m) X 2 O 3 :YO 2 (Formula II) [In the formula, 0.017<m≦0.1, X is a trivalent element, in particular X comprises one or more of aluminum and boron, preferably X comprises or is aluminum; Y is a tetravalent element, in particular, Y includes one or more of silicon and germanium, and preferably, Y includes or is silicon.

2. The zeolite of claim 1 having the molecular formula:

3. Zeolite, in its as-synthesized form, exhibits the peaks shown in Table 2 below: 【Table 2】 The zeolite has an X-ray diffraction pattern comprising:

4. The following formula III: (q) Q: (m) X 2 O 3 :YO 2 (Formula III) [In the formula, 0≦q≦0.5, 0.017<m≦0.1, Q is represented by the following formula I: 【Chemistry 1】 (Formula I) wherein R is methyl or ethyl. at least one cation selected from the 4,5,6,7-tetrahydrobenzimidazolium cations X is a trivalent element, in particular X comprises one or more of aluminum and boron, preferably X comprises or is aluminum; Y is a tetravalent element, in particular, Y includes one or more of silicon and germanium, and preferably, Y includes or is silicon.

4. The zeolite of claim 3 having the molecular formula:

5. 5. The zeolite of claim 4, wherein the structure directing agent (Q) comprises at least one cation selected from the group consisting of 1,2,3-trimethyl-4,5,6,7-tetrahydrobenzimidazolium cation, 2-ethyl-1,3-dimethyl-4,5,6,7-tetrahydrobenzimidazolium cation, and mixtures thereof.

6. A zeolite according to any one of the preceding claims which is an aluminosilicate or borosilicate and has a molar ratio Si / Al or Si / B of less than 30, preferably between 5 and 25, more preferably between 10 and 25.

7. A method for producing the zeolite according to any one of claims 1 to 6, comprising the following steps (a) to (d): (a) preparing a synthesis mixture comprising water, a source of an oxide of a tetravalent element (Y), a source of an oxide of a trivalent element (X), a structure directing agent (Q), optionally a source of hydroxide ions (OH), and optionally a source of an alkali metal element and / or an alkaline earth metal element (M); The structure directing agent (Q) has the following formula I: 【Chemistry 2】 (Formula I) wherein R is methyl or ethyl. and wherein the cation is selected from the group consisting of 4,5,6,7-tetrahydrobenzimidazolium cations of the formula: the molar ratio of Y / X in said synthesis mixture is less than 30; When a source of fluoride (F) is present, the molar ratio of F / Y is less than 0.05; process, (b) heating the synthesis mixture under crystallization conditions comprising a temperature of from 100° C. to 200° C. for a time sufficient to form crystals of the zeolite; (c) recovering at least a portion of the zeolite from step (b); (d) Optionally, treating the zeolite recovered in step (c) to remove at least a portion of the structure directing agent (Q). A method comprising:

8. 8. The method of claim 7, wherein the structure directing agent (Q) comprises at least one cation selected from the group consisting of 1,2,3-trimethyl-4,5,6,7-tetrahydrobenzimidazolium cation, 2-ethyl-1,3-dimethyl-4,5,6,7-tetrahydrobenzimidazolium cation, and mixtures thereof.

9. 9. The method according to claim 7 or 8, wherein the structure directing agent (Q) is in the form of a halide, hydroxide or nitrate, preferably the structure directing agent (Q) is in its hydroxide form.

10. the trivalent element X is selected from the group consisting of aluminum, boron, and combinations thereof, preferably aluminum; The method according to any one of claims 7 to 9, wherein the tetravalent element Y is selected from the group consisting of silicon, germanium and combinations thereof, preferably silicon.

11. The synthesis mixture had the following composition in terms of molar ratios: 【Table 3】 The method according to any one of claims 7 to 10, comprising:

12. 12. The method according to any one of claims 7 to 11, wherein the synthesis mixture comprises a source of fluoride (F) and the molar ratio of F / Y is between 0 and 0.02, more preferably between 0 and 0.01, and most preferably the synthesis mixture is substantially free of fluoride (F) ions.

13. A process for converting an organic compound into a conversion product, the process comprising contacting the organic compound with a zeolite according to any one of claims 1 to 6.